KOMUNIKASI TERAPEURIK DALAM KESEHATAN GIGI DAN MULUT DI RSGM LADOKDI TNI AL R.E. MARTADINATA - handayani, Farida (AKG Puskesad, 2023)
Communication in nursing can be known as therapeutic communication which aims to help clients solve problems, or encourage clients to take good actions for healing and improving their health. In fact, there are still dental and oral therapists who do not carry out therapeutic communication. Objective: to find out the description of the application of therapeutic communication in dental and oral examinations. Methods: Descriptive analytic method with